ONTOLOGICAL PAREIDOLIA AND THE SAFE DISSIPATION HYPOTHESIS: TOWARD A NON-REIFIED LEGAL ONTOLOGY - de Farias, Flávio Furtado; Vieira Filho, Francisco de Sousa (Seven Editora, 2026)
The article proposes the concept of ontological pareidolia as a diagnostic tool to examine processes of conceptual reification in contemporary law. It begins from the hypothesis that successful legal theories tend, progressively, to shift from analytical instruments to implicit ontological assumptions, operating not only as interpretive lenses but as supposedly neutral transparencies of the legal object itself. The phenomenon is analyzed through the theory of the balancing of principles developed by Robert Alexy, chosen as a paradigmatic case not because of structural defect, but because of its institutional success and practical diffusion. Three recurring diagnostic triggers are identified: (i) grammatical agency of concepts, (ii) colonization of the central question of the case, and (iii) inflation of defensive qualifications. It is argued that such dynamics do not constitute a theoretical error, but rather a predictable outcome of paradigmatic consolidation. The study does not seek to invalidate specific theories, but to offer a reflective protocol for the analysis of judicial decisions and normative arguments, distinguishing the conscious instrumental use of concepts from their consolidated ontological reification. In conclusion, it is suggested that the problem may be better understood in light of a broader relational ontology, according to which concepts persist insofar as they remain compatible with the institutional fields that sustain them.